2020
DOI: 10.3390/en13153763
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ammonium Nitrate(V) Porous Prill Assortments and Absorption Index on Ammonium Nitrate Fuel Oil Blasting Properties

Abstract: Ammonium nitrate fuel oil (ANFO) samples, which were obtained by blending two different types of ammonium nitrate porous prills (i.e., AN-PP7 and AN-PP8) with fuel oil (FO) were studied. Measurements of structure, crystallinity and morphology were performed using X-ray Diffraction (XRD), Infrared Spectroscopy (IR) and Scanning Electron Microscopy (SEM), respectively. From the SEM analysis, it was indicated that a “wrinkled” structure characterized the crystal surface of the samples, which were based on two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“… 37 However, there are some surface-active substances present during the oil blasting stage such as asphaltenes. 38 When the water cut is below 50%, flow shear produces a relatively stable brine/oil emulsion in which the aqueous phase is sufficiently disseminated in the oil phase. This stage is classified as an oil-based system.…”
Section: Hydrate-plugging Mechanism In the Multiphase Systemsmentioning
confidence: 99%
“… 37 However, there are some surface-active substances present during the oil blasting stage such as asphaltenes. 38 When the water cut is below 50%, flow shear produces a relatively stable brine/oil emulsion in which the aqueous phase is sufficiently disseminated in the oil phase. This stage is classified as an oil-based system.…”
Section: Hydrate-plugging Mechanism In the Multiphase Systemsmentioning
confidence: 99%
“…Furthermore, rising temperature led to the thermal decomposition of AN, which was confirmed by the appearance of the fourth DSC peak with a maximum at ca. 287–293 °C [ 46 , 61 ]. From the analysis of DSC profiles, it may be concluded that the modification route of ANFO with zeolite Y has a small influence on the decomposition temperature of prepared non-ideal explosives.…”
Section: Resultsmentioning
confidence: 99%
“…Post-blast fumes analysis was conducted according to the procedure described in [ 44 ], which was based on regulations reported in [ 45 ]. The description of blasting tests has also been reported in our previous works [ 41 , 46 , 47 ]. In each experiment, 600 g of non-ideal ANFO charge was placed inside the steel mortar locked in the blasting chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, they contain a nitro group for example TNT [19] or nitroglycerin [20]; • Tertiary or "propellants" they are almost insensitive to shock and triggering and to detonate they need secondary charges that amplify the triggering effect of the primary explosives. For example, ammonium nitrate fuel oil (ANFO) [21,22] and potassium chlorate fuel-oxidizer [23].…”
Section: Introductionmentioning
confidence: 99%